Efficacy of Food Safety Training in Commercial Food Service. Issue 6 (8th May 2019) - McFarland, Patricia; Checinska Sielaff, Aleksandra; Rasco, Barbara; Smith, Stephanie
Abstract : Abstract: Proper food safety training is essential to decrease incidences and overall rates of foodborne illnesses and outbreaks. Though many commercial restaurants should provide proper food safety training to food handler employees, this training is not always offered or effective. Here, we summarize the results of a primary literature study concerning the effectiveness of food safety training in commercial settings. The literature chosen for review contained only studies with experimental food safety training, with before and after training data. Through evaluation of these studies, the best practice for ensuring effective training and follow‐through were the use of food safety training programs, which incorporated both knowledge and behavior‐based training. Practical Application: Food safety managers in food service establishments may consider reevaluating their current food safety training program to incorporate behavioral‐based food safety training in addition to knowledge‐based training.